2018
DOI: 10.5194/acp-2018-869
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simulations of black carbon (BC) aerosol impact over Hindu-Kush Himalayan sites: validation, sources, and implications on glacier runoff

Abstract: <p><strong>Abstract.</strong> We estimated the black carbon (BC) concentration over the Hindu Kush Himalayan region (HKH), its impact on snow-albedo reduction and sensitivity on annual glacier runoff over the identified glaciers. These estimates were based on free-running aerosol simulations (<i>freesimu</i>) and constrained aerosol simulations (<i>constrsimu</i>) from an atmospheric general circulation model, com… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Many of these studies used online global model simulations at coarse spatial resolutions of ∼ 50-150 km (Flanner and Zender, 2005;Ming et al, 2008;Qian et al, 2011;Kopacz et al, 2011;Zhang et al, 2015). Other studies employed offline simulation of the snow albedo effect using measured or modeled concentrations of deposited LAPs in surface snow or estimated from atmospheric loading and ice cores Nair et al, 2013;He et al, 2014;Santra et al, 2019;Thind et al, 2019). The complex terrain of HMA, seasonal snowfall and near-surface air circulation are not well resolved by coarse global climate models (Kopacz et al, 2011;Ménégoz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies used online global model simulations at coarse spatial resolutions of ∼ 50-150 km (Flanner and Zender, 2005;Ming et al, 2008;Qian et al, 2011;Kopacz et al, 2011;Zhang et al, 2015). Other studies employed offline simulation of the snow albedo effect using measured or modeled concentrations of deposited LAPs in surface snow or estimated from atmospheric loading and ice cores Nair et al, 2013;He et al, 2014;Santra et al, 2019;Thind et al, 2019). The complex terrain of HMA, seasonal snowfall and near-surface air circulation are not well resolved by coarse global climate models (Kopacz et al, 2011;Ménégoz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Historical BC records from the Tibetan glacier ice cores revealed the impact of anthropogenic emissions, with BC concentrations increased by 2−3 times since the 1950s (Kaspari et al, 2011;Wang et al, 2015. Light absorbing BC and OC (including water soluble organic carbon (WSOC) and water insoluble organic carbon (WIOC)) deposited on the glacier and snow cover induced surface darkening and enhanced melting (Flanner et al, 2007;Kang et al, 2020;Lau and Kim, 2018;Santra et al, 2019;Xu et al, 2009;Zhang et al, 2020b). Estimates indicated that BC in snow resulted in accelerated glacier melt by approximately 15−20% in the southeast/central TP and Central Asia (Li et al, 2020;Zhang et al, , 2020b reduced snow cover duration by 3−4 days across the TP and 3−6 days in Northern Xinjiang (Zhang et al, 2018a;Zhong et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In addition to this warming, the reduction of surface ice albedo by ice surface deposits of dark colored impurities constitutes an additional control of glacier melting rate. [5][6][7] Impurities that darken the ice surface and directly increase the heat absorption and thus enhance ice melting comprise dust, BC (black carbon, e.g., soot), and other forms of OC not derived from combustion. [8][9][10][11] In this study, OC refers to the total organic 51 carbon that comprises the entire pool of organic carbon including both organic and elemental 52 carbon.…”
Section: Introductionmentioning
confidence: 99%
“…Further, we classify the OC as OC ff (fossil fuel) and OC bio (biomass) referring to OC derived from either fossil fuel or biomass sources, such as biomass burning derived particles, atmospheric organic matters, and glacial microbes. 5 The contribution to glacier surface darkening by particle matter and its attendant impact on glacial melt across high Asian mountain glaciers is variable. For example, the main contributor to glacier surface warming in Eastern Himalaya and Central Asia is BC, while mineral dust is a dominant factor in the western Himalaya.…”
Section: Introductionmentioning
confidence: 99%